Breaking Bad News: Flipped Calendar as a Patient Information Provision Education Media Using the Spikes Method a Universitas Gadjah Mada Academic Hospital - Wirastuti, Fita; Effendy, Christantie; Adnan, Nur Fatimah; Satiti, Sekar (Academic Hospital Journal, 2025)
Background: The quality of Breaking Bad News (BBN) communication has a significant impact on patient treatment adherence, emotional condition, understanding, and satisfaction with medical care. Effective communication skills and appropriate communication techniques are essential for providing optimal care. The SPIKES protocol is a communication protocol used as a standard and strategy for delivering difficult patient communication, comprising several stages: setting up, perception, invitation, knowledge, emotions, strategy, and summary.Objective: This study aimed to determine the effect of using the BBN flip chart calendar as educational media, combined with the SPIKES method, at Universitas Gadjah Mada Academic Hospital (UGM Academic Hospital). The specific research objectives were: (a) to understand the perceptions and expectations of doctors and nurses when providing education related to BBN, and (b) to determine the effect of using the BBN flip chart calendar educational media on patients.Method: This study was an experimental investigation to assess the effectiveness of using the BBN flip chart calendar as educational media in conjunction with the SPIKES protocol. The type of research was a quantitative study to understand the implementation of the BBN flip chart educational media at UGM Academic Hospital.Result:  The intervention group and the control group do not show statistically significant differences. The primary reason for these outcomes could be that behavioral changes are difficult to modify with a single communication practice. Continuous evaluation and feedback are needed on the effectiveness of BBN to improve the quality of health workers.